Personal Constructions of Parental Influence Relatied to Career Development - Young, Richard A.; Friesen, John D.; Dillabough, Jo-Anne M. (Canadian Journal of Counselling and Psychotherapy, 2011)
Psychological researchers, influenced by sociological and ecological approaches to human development, have begun to question the lack of attention to interactive processes in the family related to the career development of adolescents and young adults. The purpose of the present study was to explore the ways parents and young adults socially construct the interactive domain of parental influence. A sample of 279 parents and young adults were randomly assigned to complete a Q-sort set describing various family activities and interactions thought to influence career development Consistent with Qmethodology, factor analyses were conducted for subjects rather than items, followed by qualitative analyses. Results revealed that interactions perceived as key elements in career development refer to either the process or outcomes of parental influence and address responsibility, autonomy, open communication, support and encouragement, and direction and guidance. The results are discussed in light of the theoretical perspective proposed